Aspek Reproduksi Ikan Nyalian (Barbodes binotatus Valenciennes, 1842) di Danau Tamblingan - Ni Made Sita Aditya Putri; Nyoman Dati Pertami; Gde Raka Angga Kartika (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
The reproduction aspects of spotted barb (Barbodes binotatus Valenciennes, 1842) in Tamblingan Lake are not yet known, so that efforts to manage the resources of this fish cannot be carried out. This study aims to determine the reproduction aspects of spotted barb in Tamblingan Lake. Sampling was conducted from January to June 2019. This research used descriptive and quantitative methods. Purposive sampling method used for catched the spotted barb at five stations. Sampling was done once in a month. The fish were collected used gill net with a mesh size of 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 cm. The samples of spotted barb that found during data collection were 208 individuals. The results showed that the ratio between the sex ratio of male and female spotted barb was 1.17: 1 which indicates a balanced sex ratio, with the gonad maturity stage of male fish more varied (I-IV) than female fish (III and IV). The highest average gonadosomatic index (male and female) was found in March and the lowest in January. The fecundity ranges from 57-23,897 eggs.